Efficacy Of Concrete Roof Tiles Composite Using Clay And Rice Straw Fibre As Heat Insulation Material - Rased, An Nisha Nur Welliana Abd (2019)
Currently, concrete roof tile composite (CRTC) with various properties improvement is frequently used for roof covering. This is mainly due to the advantages such as they are very durable and last for many years, can withstand high winds better than other materials, lower costs involved, more readily available and also production is high because it is easily manufactured. This research mainly focuses on the engineering, durability, and thermal properties of concrete roof tile (CRT) that were produced with various ratios of clay and rice straw fibre. The impacts of different lengths of rice straw fibre were also tested in this study. The CRT properties were tested followed ASTM C1492 - 03(2016) Standard Specification for Concrete Roof Tile and the workability of this CRT was tested according to Standard Test Method for Flow of Hydraulic Cement Mortar (ASTM C1437). Thermal performance like thermal conductivity, specific heat capacity and thermal diffusivity was measured using Hot Disk Thermal Constants Analyser Model TPS 2500. Besides that, the infrared thermography (IR image) was used to reveal the expected thermal behaviour of concrete with 10% clay and 1% rice straw (0.1 cm-2.0cm) C10RS 1A compared to control concrete (CO) sample. Indoor thermal performance was measured by using actual house model and IESVE simulation method. After that, the data from these two methods were compared and utilized in order to obtain the CO sample data via IESVE simulation. Results from the entire test proved that C10RS 1A sample with clay and rice straw has low engineering properties but it is lightweight, high shock resistant and high water resistance.